Philosophy as an Academic Discipline for Technical Undergraduates and Specialist Degree Students - D. N. Bezgodov; E. A. Vologin; S. V. Shilova (Высшее образование в России)
The article focuses on substantiating a number of didactic principles and content components of the course of philosophy for undergraduates and specialist degree students of technical majors.The authors ground the interpretation of the subject and method of philosophy as a reflexive analysis of so called “inevitable” experience, and the values as its significant segment. The study of higher social values and the method of their analysis is considered as a key prerequisite for learning the discipline “management” by students, and, in particular, the theory of organizational culture, which can be viewed as a basis for the development of future bachelors’ and specialists’ managerial competencies. The authors dwell on the key role of philosophy in the study and acceptance of a certain worldview paradigm. The themes “Civilization approach” and “Russian philosophy” are presented as instruments for the content integration of classroom and extracurricular forms of students’ patriotic education